(untitled) (GEON Journal (Management, Organizations and Business), 2020)
Taking into account that the climatic conditions throughout the world due to the green house effect, generating that the temperature has been growing, affecting in one way or another the social, economic and environmental aspects, as reported by Ideam and Fonade and reinforced by the magazine agribusiness. Farmers currently do not have the necessary tools to be able to carry out a technical study and define the precise time for quality cultivation of each of their products. Using the arima estimation model, the temperature, humidity, velocity, pressure data released by a weather station (Standard Station) were related to a predictive mathematical model. As a first part of the modeling of the system, a “Wunder Station” brand station was acquired and located in Yurimena - Cofrem (Km 33, avenue Puerto López) where for six months data from the different meteorological variables were collected, these results were analyzed using E-views (software) and were parameterized in order to establish an accuracy of 95%. As a result of this prediction model, it is sought to estimate the different environmental variables in this region for agricultural purposes. The prediction model will be the basis for the design and implementation of a weather station created from the research group of the Panamericana University Foundation. With the data obtained during this period, a 45-day prediction was established with an error rate of 0.4%, allowing the analysis of other variables such as relative humidity, wind speed, among others.